Who is Dayani Cristal? - Heiblum, Leonardo (Kino Lorber, 2014)
Tells the story of a migrant who found himself in the deadly stretch of desert known as "the corridor of death" and shows how one life becomes testimony to the tragic results of the U.S. war on immigration. As the real-life drama unfolds we see this John Doe, denied an identity at his point of death, become a living and breathing human being with an important life story
English and spanish with english subtitles. - Bonus features include role-play conversation between Gael García Bernal and migrants' rights activist Padre Alejandro Solalinde, The invisibles: a film by Marc Silver and Gael García Bernal in collaboration with Amnesty International, theatrical trailer. - Originally produced as a motion picture in 2013.
Keywords: Border crossing / Arizona; Illegal aliens / Government policy / United States; Migration; Politik; Border crossing -- Arizona; Illegal aliens -- Government policy -- United States; Grenzgebiet; Illegaler Einwanderer; United States / Emigration and immigration / Government policy; Mexican-American Border Region; USA; Arizona; Film; DVD-Video